PRINCIPLES OF ISLAMIC ETHICS IN THE ISLAMIC FOREIGN EXCHANGE SWAP IN ISLAMIC BANKING MALAYSIA - Azlin Alisa Ahmad, Mohd Hafiz Mohd Dasar, Nik Abdul Rahim NikAbdGhani (Hamdard Islamicus, 2020)
Islamic FX swap is one of the hedging mechanisms that will help financial institutions minimize foreign exchange risk as well as protects the value of assets from the market exposure. However, the Islamic Fx swaps is claimed to mimic conventional FX Swap structure which is to some degree is incompatible with Islamic financial ethics. This paper aims to analyze the application of the principles of Islamic ethics in the Islamic Foreign Exchange Swap (Islamic FX Swap) within the Islamic banking institutions in Malaysia. This study used content analysis method of the qualitative approach. This paper concludes that in Malaysia, the Islamic FX Swap operation in Islamicbanking institutions runs based on the principles of Islamic ethics. There are four principles of Islamic ethics in the implementation of Islamic FX Swap, which are the absent of riba, the absent of gharar, the prohibition of excessive speculation and the prohibition of gambling. The implementation of Islamic FX Swap